The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/cncr.33206
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of t(11;14) in multiple myeloma: Black and white or shades of gray?

Abstract: In this issue of Cancer, Badar et al report that African Americans with translocation t(11;14) multiple myeloma have excellent outcomes if they undergo early autologous hematopoietic cell transplantation followed by posttransplant maintenance, with the overall survival superior to White t(11;14) patients on multivariable analysis. Ongoing clinical trials on venetoclax‐based combination therapies in multiple myeloma should actively recruit minority populations such as Blacks, Asians, and Hispanics to identify a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Patients with this specific translocation have a unique myeloma type and are less likely to be hyperdiploid ( 17 ). They show a two-fold increased incidence of light-chain or non-secretory myeloma, are more likely to present with bone disease, and harbor uncommon heavy-chain isotypes such as immunoglobulin M (IgM) or IgE ( 10 , 39 42 ). Malignant PCs are less mature with scant cytoplasm, have a lymphoplasmacytic phenotype with CD20 expression in roughly half of the cases and, most critically, are prone to apoptosis through the anti-apoptotic protein BCL2, which is the target for venetoclax ( 39 , 40 , 43 ).…”
Section: Translocation T(11:14) In Mm: Update On Molecular and Clinic...mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with this specific translocation have a unique myeloma type and are less likely to be hyperdiploid ( 17 ). They show a two-fold increased incidence of light-chain or non-secretory myeloma, are more likely to present with bone disease, and harbor uncommon heavy-chain isotypes such as immunoglobulin M (IgM) or IgE ( 10 , 39 42 ). Malignant PCs are less mature with scant cytoplasm, have a lymphoplasmacytic phenotype with CD20 expression in roughly half of the cases and, most critically, are prone to apoptosis through the anti-apoptotic protein BCL2, which is the target for venetoclax ( 39 , 40 , 43 ).…”
Section: Translocation T(11:14) In Mm: Update On Molecular and Clinic...mentioning
confidence: 99%
“…African Americans or individuals with a high degree of African ancestry have an increased prevalence of the t(11;14) translocation (36,37). This finding may partially explain the influence of race on prognosis and outcomes in MM, a complex subject with conflicting results under investigation (38,39).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that patients with t(11;14) should be considered as standard-risk ( 4 , 7 , 17 ), while other argued that t(11;14) was a negative indicator associated with inferior survival to other standard-risk patients, especially in novel agent era ( 6 , 18 , 19 ). In general, t(11;14) was recognized as a group of heterogeneous disease, which had shown huge discrepancies in outcomes ( 11 , 20 , 21 ). Herein we obtained credible data from 211 newly diagnosed MM patients with t(11;14) and analyzed whether CD20 expression detected by flow cytometry could further separate the different prognosis outcomes of t(11;14).…”
Section: Discussionmentioning
confidence: 99%
“…( 12 ) also reported a slow onset of response while comparable best response and longer survival of CD20 positive MM patients. Considering the fact that patients with t(11;14) usually exhibited a decreased proliferative index and a lower deep response rate ( 20 , 30 ), it could be speculated that CD20 positive t(11;14) myeloma referred to a more indolent clinical course with a better outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that t(11;14) behaved rather like an "intermediate-risk" disease, since all outcomes were inferior compared to the patients with no translocation and superior to those with non-t (11;14). The impaired effectiveness of PIs in inducing endoplasmic reticulum stress [24] and the negative impact of bortezomib-based therapy regimens in t(11;14) light-chain amyloidosis could be responsible for the inferior response rates in these special patient cohorts [41,42].…”
Section: Dynamic Role Of T(11;14) In Shaping the MM Prognosis Landsca...mentioning
confidence: 99%